Patients' experience and perspectives on the rational use of drugs in Turkey: a survey study - (:unkn) unknown (DOVE MEDICAL PRESS LTD, 2012)
Aim: Physicians' inappropriate prescribing habits affect patients' lives both medically and financially. To avoid these unwanted situations, the World Health Organization defined the rational use of drugs (RUD) in 1985. This study aimed to investigate whether patients were as informed about their diagnosis and medication as anticipated and their knowledge about the RUD in general. Methods: A questionnaire was given to 260 patients being treated at the Kartal Training and Research Hospital between February and March 2012. Results: Most of the patients declared that they were not informed enough about their diagnosis and not all of the physicians evaluated their therapies. These undesirable conditions were due to high daily examined patient numbers. A total of 68.6% of patients stated that time allotted per patient was 0-10 minutes, 33.1% found the information given sufficient, and 11.3% were told to repeat back narratives about their treatments. Instructions and warnings given by physicians about prescribed drugs did not fully meet the RUD criteria. The majority of referred patients were willing to be educated about the subject. Conclusion: These results showed that heavy patient load seriously affects the RUD process. Improvement of the current health system should be given serious consideration. After sufficient arrangements have been made in this field, patients will be able to be informed properly about medicines prescribed by their physicians. Also, public education programs will be helpful to raise awareness of the subject on a larger scale.
Keywords: rational use of drugs; prescribed medicine; patient load; medical information; public education; GENERAL-PRACTITIONERS